Investigations of BaCl2:Eu2+ nanophosphor using electron paramagnetic resonance, structural analysis and thermoluminescence - Secu, C.E.; Rostas, A.M. (Journal of alloys and compounds, 2020)
Structural analysis of the Eu2+-doped BaCl2 nanocrystals and the doping process was monitored and characterized via electron paramagnetic resonance spectroscopy. Structural analysis has shown a slight distortion of the cell which is reflected in the low value of microstrain and the Eu2+-doping effect is limited to the first order chlorine ions neighbors of Ba2+. Electron paramagnetic resonance measurements have indicated the presence of the Eu2+-dopant ions in the BaCl2 host matrix with a solubility limit of about 2%. From the spectra simulation, the isotropic g-value giso = 1.9951(7), the isotropic hyperfine coupling constant Aiso = 42.4 MHz and the high-order zero-field splitting parameters from the crystal field B20 = 21 MHz and B22 = -493 MHz were obtained. During X-ray irradiation, defects are produced and stabilized by the Eu2+ dopant ions. The single dominant thermoluminescence peak at 132 °C (activation energy E = 1.1 eV) was assigned to the recombination of the F(Cl)-center with Eu2+ related hole centers. •Resolved crystalline structure of the Eu2+-doped BaCl2 nanocrystals.•Maximal dopant concentration was determined via EPR.•Spin system parameters were determined with high precision through EPR spectra simulations.•X-ray induced radiation effects have been investigated using thermoluminescence and EPR techniques.•X-ray irradiation of the subject material, induced new defects that are stabilized by the Eu2+ dopant ions.